Validity and reliability of the Balance Tracking System during feet together stance. (October 2018) - Murray, Nicholas G.; Grotewold, Cody; Szekely, Brian; Powell, Doug; Munkasy, Barry
Highlights: BTrackS is a clinical tool that measures center of pressure changes. Force platform is the gold standard of center of pressure analysis. BTrackS is a valid tool of center of pressure analysis. BTracks is a reliable assessment instrument across a 48–72 h period. BTracks underestimates center of pressure changes in various conditions. Abstract: Laboratory and clinical measures of postural control are commonly used in the diagnosis of concussion. A novel instrument, the Balance Tracking System (BTrackS), has similar instrumentation to a force platform (FP), with greater portability and reduced cost. The purpose was to evaluate the concurrent validity of derived center of pressure (CoP) excursion and mean velocity for the raw CoP coordinates produced by the BTrackS and FP during feet together quiet upright stance. Participants stood on the BTrackS and FP at two time points. The BTrackS excursion values were significantly lower than the FP values at both time points but the devices CoP excursion values were strongly related at both time points and in all conditions. For mean velocity data, there were no significant differences between the devices at any time point. The BTrackS had excellent test–retest reliability over time in all conditions for both the excursion and mean velocity data.